Metode Double-Difference Untuk Merelokasi Hiposenter Gempabumi Susulan Seririt Singaraja - Winardi Tjahyo Baskoro; I Gde Antha Kasmawan; I Ketut Putra; Ni Nyoman Ratini; Sismanto (Kappa Journal, 2024)
A method that does not require a main earthquake (master event) that can be used simultaneously to relocate a very large number of earthquakes with wide hypocenter separation is called the double-difference method. A method used to relocate the aftershocks in Seririt Singaraja on November 14 2019 with coordinate positions 113.478 – 115.181 East Longitude and 8.357 – 7.894 South Latitude. The earthquake data used in this research was accumulated from 85 BMKG seismic stations. Data analysis uses cross-correlation time differences which can increase the accuracy of travel time between the receiving station and the earthquake, thereby reducing errors in calculations. The double difference method used to relocate the earthquake in the Seririt Singaraja area showed that there was a shift in the location of the earthquake hypocenter before and after it was relocated. Horizontally and vertically, the distribution of earthquake hypocenters before and after being relocated occurs when there is a collection of location shifts. The results of this research were able to relocate 152 aftershocks properly. The main earthquake after being relocated was at a depth of 17 km, while the distribution of aftershocks was at a depth of around 6-25 km, so that it can more accurately describe the position of the earthquake source and is able to show clearer and easier to interpret structural patterns.